RULES PROPOSED TO CURB SMOKING IN FEDERAL OFFICES (Tufts Archival Research Center, 2007)
Associated Press article on smoking regulations in federal offices proposed by the General Services Administration (GSA). Quotes the GSA saying the regulations are for health reasons and that the regulations would have "more weight and authority" than current regulations.